THE ALGERIAN NATIONAL LIBERATION MOVEMENT AND ITS ROLE IN THE FRENCH COLONIAL SYSTEM - Rasulov Otabek Abdulazizovich (International Journal of Business, Law and Political Science, 2025)
Objective: The French colonialism in Algeria had features of a specific settlement colonization type through expropriating vast lands and transformation of population. While settler colonialism has been extensively studied, the enduring legacy of this regime on Algeria´s socio-political and economic structures, and relations with France, both during and after colonialism remain too often unexplored. This article examines the origins of the Algerian War of Independence, tracing the development of nationalist movements and the emergence of the National Liberation Front (FLN). Method: Wherever the French established colonies, they did not consider such colonies to be mere colonies like others; in Algeria, settlers seized control of all the best land, forcing the native population onto the dry and barren soils. European settlers, lured to settle by the French government, rang the political and economic bell in Algeria. The French enacted systems such as the Code de l’Indigénat that instituted severe limitations of local civil rights, policies that only escalated aggravation of the natives. Results: The relationship between the settler colonialism experienced in Algeria and the subsequent attempts to build a national identity during and after the revolution from French rule is one that has impacted the identity of the nation greatly and has thus been the subject of a great deal of study considering the before-during and the after of the processes which shaped the political, social and economic nature of the revolution, and the post-colonial state building process. Novelty: This study highlights the distinctive nature of French settler colonialism in Algeria as not merely administrative control but a transformation of land, population, and identity. It contributes to understanding how the colonial system’s socio-political legacy shaped both the Algerian War of Independence and the post-colonial state-building process.